Inhibition of histone deacetylase in Arabidopsis root calli promotes de novo shoot organogenesis - Qinwei Pan; Ruirui Huang; Qiong Xiao; Xuting Wu; Baoxia Jian; Yanan Xiang; Lijun Gan; Zongrang Liu; Yi Li; Tingting Gu; Huawei Liu; Huawei Liu (Frontiers in Plant Science)
De novo organogenesis from somatic cells to the entire plant represents a remarkable biological phenomenon, but the underlying regulatory mechanism, particularly at the epigenetic level, remains obscure. In this work, we demonstrate the important role of histone deacetylases (HDACs) in shoot organogenesis. HDAC inhibition by trichostatin A (an HDAC inhibitor) at the callus induction stage promotes shoot formation in wounded roots and circumvents tissue wounding to initiate shoot regeneration in unwounded roots. This HDAC inhibition-mediated promotion of shoot organogenesis in wounded roots is associated with the concomitant upregulation of the wound signaling pathway (WOUND INDUCED DEDIFFERENTIATION 4, ENHANCER OF SHOOT REGENERATION1, ISOPENTENYLTRANSFERASE 5, CUP-SHAPED COTYLEDON 2 etc.) and the ARF-LBD pathway (AUXIN RESPONSE FACTOR 19, LATERAL ORGAN BOUNDARIES-DOMAIN 29, etc.) and the downregulation of auxin biosynthesis and reduced auxin content. Furthermore, inhibiting HDACs enhances the local enrichment of histone 3 lysine 9/lysine 14 acetylation at ISOPENTENYLTRANSFERASE 5, supporting the role of histone acetylation in its transcriptional regulation. On the other hand, the HDAC inhibition-associated activation of shoot organogenesis from unwounded roots is coupled with increased expression of the ARF-LBD pathway gene LATERAL ORGAN BOUNDARIES-DOMAIN 29 while bypassing the wound signaling or auxin biosynthetic genes. These findings provide novel insights into the regulatory mechanisms underlying de novo shoot organogenesis and lay a foundation for the improvement of plant transformation technologies.